Cyberbullying and Cyber Abuse Intervention: The Three-Tiered Model for Schools. Issue 3 (1st October 2016) - Davis, Nancy; Schmidt, Caryn
ABSTRACT: This article describes a three-tiered model that school personnel can implement to address cyberbullying, sexting, and other abusive social media behavior prevalent in schools. This model addresses prevention, intervention, and monitoring at multiple levels in a school community. It is designed to provide preventative services to all stakeholders in a school community, and to target those with moderate or significant problems.